Firm valuation and corporate governance of politically connected firms in Singapore. - Lee, Sin Wei. (2008)
In this paper, we explore the relationship between political connection and firm value of newly listed companies in Singapore from 1997-2002. Using Tobin’s Q as a proxy for firm value, the objective of this paper is to investigate whether there is a significant difference between politically connected firms and those that are not. We find that, in Singapore where corruption is low, political connection does not contribute significantly to firm value. These results are consistent even after we have controlled for firm specific characteristic such as firm size, leverage ratio, profitability, year of listing and industry type. At the end of the report, we also find that corporate governance in Singapore is not an important factor in explaining the variation of firm value in the short run. Robustness checks are performed, showing that a number of alternative political connection variables produce similar results.